Changing Primary Students' Perceptions of Teacher Interpersonal Behaviours in Science - Waldrip, Bruce; Reene, P.; Fisher, Darrell; Dorman, J. (Kluwer Academic Publishers, 2008)
The paper reports on part of a large-scale study aimed at examining students’ perceptions of teacher–student interactions. This paper will report on a study utilising mixed methodology in 12 Queensland primary classrooms. After the students’ perceptions were established, the teachers, through a consultative process, developed strategies to change the students’ perceptions of their classroom over a 3 month period. The paper reports on what strategies these teachers utilised and what changes in students’ perceptions resulted. The classroom teachers were interviewed about the change in students’ perceptions, what changes they had sought to promote in their classrooms, and what they felt had been achieved in their classrooms. The study found that students were able to articulate what changes the teacher had implemented, what their reaction was to these changes and their perception of the classroom environment as a result of these implemented strategies.